Spatio-temporal water uptake patterns of tree saplings are not altered by interspecific interaction in the early stage of a subtropical forest - Trogisch, S; Salmon, Y; He, J; Hector, A; Scherer-Lorenzen, M (Elsevier, 2016)
Complementary resource use has often been claimed to explain positive effects of plant diversity on ecosystem functioning, but the underlying mechanisms of complementarity have rarely been directly quantified in forest systems. The aim of this study was to characterize spatial and temporal water uptake of subtropical tree saplings, to assess the role of interspecific interaction on water uptake patterns and to quantify species niche breadth and overlap. Our experiment comprised two deciduous (Castanea henryi, Quercus serrata) and two evergreen tree species (Elaeocarpus decipiens, Schima superba) that were each planted in monoculture and 4-species mixture. We used deuterium-enriched water to trace seasonal water uptake from 5 cm and 20 cm soil depth. Castanea exploited predominantly the upper soil (74% of overall tracer uptake across treatments) whereas Quercus (50%), Elaeocarpus (57%) and Schima (62%) tended to use both soil layers more equally. Species identity had an overall significant effect on isotopic enrichment in stem water. There was no effect of species richness: niche breadth and overlap of single species was not affected by interspecific interactions in mixtures. Niche overlap between deciduous species was lowest (74%) whereas the two evergreen species had similar water uptake patterns (91%). According to our results, interspecific competition did not alter water uptake patterns of the studied species during the early phase of forest establishment. Thus, soil water uptake complementarity could only occur through inherent (fundamental) specific differences in water uptake niches based on sapling specialization, while phenotypic adjustments to interspecific interaction or neighbor diversity are less important.